Enhanced boron removal from metallurgical grade silicon by the slag refining method with the addition of tin. Issue 9 (12th June 2016) - Li, Jiayan; Cao, Panpan; Ni, Ping; Li, Yaqiong; Tan, Yi
ABSTRACT: An effective boron removal method was developed through a process of combining Si–Sn alloy with slag treatment. Boron content in refined silicon and boron removal fraction by slag containing 5 wt% CaO, 25 wt% SiO2 and 70 wt% Na2 SiO3 and was investigated under varied Si–Sn alloy composition, slag/Si–Sn alloy mass ratio and refining time. Boron was effectively removed by adding tin to metallurgical grade silicon. In particular, the boron content in metallurgical grade silicon decreased from 12.92 ppmw to 0.79 ppmw by adding 50 at% tin under a mass ratio of 2:1 (slag:alloy) at 1723 K. The amount of boron removed increased with increasing amount of tin added, mass ratio and refining time.